PLATELET RICH PLASMA PREPARATION PROTOCOLS: A PRELIMINARY STUDY - Nugraha, Hans Kristian; Muljanti, Meiti; Hernaningsih, Yetti; Nugraha, Jusak (Institute of Topical Disease, 2012)
Currently, therapy with Platelet Rich Plasma (PRP) has been widely used and continues to grow for various clinical applications. Along with its development, there are various options in the method of obtaining PRP, either automatic or manual, while one of the most reliable methods according to the literature is a double centrifugation method. The purpose of this research is to produce anoptimization of the double centrifugation method. This study used experimental data obtained by conducting a research at the Clinical Pathology Laboratory of Dr. Soetomo Hospital, Surabaya. Experiments were conducted on stored blood obtained from the blood bag from Indonesian Red Crossand fresh blood from healthy donors with CPD anticoagulant. Results: PRP with optimum platelet count could be made with sufficient personal laboratory skills and amounted to 4.11 times with the platelet count of 1.152 million using 1300 rcf for 5 minutes for the first centrifugation, and 2300 rcf for 7 minutes for the second centrifugation.